Between-country global inequality and demographic change - Bruni, Michele (Penerbit Universiti Kebangsaan Malaysia, 2022)
This paper revisits the debate over between-country inequality with a focus on demographic factors. We argue that population growth has played an important role in facilitating per capita income convergence of middle- and high-income countries while leaving low-income countries behind relative to both the global average and the high-income countries. According to our assessment, the exceptional economic performance of China, in contrast to India, is the result not only of an extremely high rate of GDP growth but also of a very limited increase of total population. The second part of the paper suggests that the demographic transition process, affecting the three major age groups in their natural order, generates several interlinked challenges -- the education challenge, the employment challenge, and the migration challenge. And it is the capacity to successfully confront these challenges that partly explains the differential economic performance of the two Asian giants - China and India -- as well as a number of Low-Income Countries and High-Income Countries. In the next decades, the demographic transition will create a “demographic polarization” between rich countries, leaving them in a structural shortage of labour. On the other hand, poor countries will be affected by a structural excess of labour making mass migration unavoidable. Whether these contrasting forthcoming demographic shifts widen between-country gap per capita income gap will critically depend on the global governance of migration flows.